Modified ECMP Routing Using Adapted Cost Disjoint Multiple Paths ACDMP - Jasim, Abbas A. (Iraqi Journal for Electrical and Electronic Engineering, 2015)
Computer network routing is performed based on routing protocol decisions. Open Shortest Path First OSPF is the most known routing protocol. It suffers from congestion problem since it generally uses single (least cost) path to deliver information. Some times OSPF delivers information using more than one path in the case of more than one path have the same cost value. This condition is rarely achieved in normal cases. In this work OSPF is developed to distribute information load across multiple paths and makes load distribution as general case for the routing protocol. The modification supposes no protocol replacement and uses the existing protocol facilities. This makes faster information delivery, load balancing, less congestion, and with little modification on the built in OSPF functions. Disjoint paths are calculated then the costs of the best set of them are adapted using approporate ratio.